KETIDAKADILAN GENDER PADA PEREMPUAN DALAM NOVEL ENTROK KARYA OKKY MADASARI - Endah Maria Ulfah (Buana Bastra, 2018)
This research is made because the occurance of the unfairness gender to the woman inEntrok novel by Okky Madasari that effects woman resistance to gain gender equality. Thepurpose of the research is to describe the unfairness gender and woman resistance in Entrok novelby Okky Madasari by using gender unfairness analysis based on sosialist feminism theories. Thisresearch uses descriptive qualitative method. The gender unfairness of woman in Entrok novel iscaused by man’s opinion that is sevoregein in a relative or a sociaty or called by domination ofpatriarki. it influences sociaty’s culture and tradition. It causes misunderstanding between societyabout what is gender and sex. That gender unfairness is a booster of feminism movementapperance. It appears because of the meaning of gender that is not understood well by the society.Feminism movement which is done by woman is a woman resistance caused by unfairnessgender that adverses herself.Based on the data analysis the researcher found five kinds ofunfairness of woman that effects domination of patriaki. It causes gender unfairness. Those arestereotype, subordination, marginalization, double burden, and violence to the woman. Genderunfairness makes the woman do resistance and demands equity for herself. There are sevenresistences that is done by woman in Entrok novel. Those are the resistance to the stereotip thatwoman is weak and man is strong, the resistance to the stereotip that woman who becomes thesecond wife is called a bitch. The resistance to the marginalization in occupation, the resistance tothe marginalization in household, the resistance to the marginalization caused by govermentpolicy, the resistance to the double burden cause by patriaki system and resistance to the violenceand rape. But all of the resistances that are done is note able to change gender unfairness happens.This because of man’s patriaki domination that is valided by culture construction that is increasingly glutinous in society’s opinion.